Concomitant Hepatorenal Dysfunction and Malnutrition in Valvular Heart Surgery: Long‐Term Prognostic Implications for Death and Heart Failure - Yi‐Kei Tse (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Strategies to improve long‐term prediction of heart failure and death in valvular surgery are urgently needed because of an increasing number of procedures globally. This study sought to report the prevalence, changes, and prognostic implications of concomitant hepatorenal dysfunction and malnutrition in valvular surgery. Methods and Results In 909 patients undergoing valvular surgery, 3 groups were defined based on hepatorenal function (the modified model for end‐stage liver disease excluding international normalized ratio score) and nutritional status (Controlling Nutritional Status score): normal hepatorenal function and nutrition (normal), hepatorenal dysfunction or malnutrition alone (mild), and concomitant hepatorenal dysfunction and malnutrition (severe). Overall, 32%, 46%, and 19% of patients were classified into normal, mild, and severe groups, respectively. Over a 4.1‐year median follow‐up, mild and severe groups incurred a higher risk of mortality (hazard ratio [HR], 3.17 [95% CI, 1.40–7.17] and HR, 9.30 [95% CI, 4.09–21.16], respectively), cardiovascular death (subdistribution HR, 3.29 [95% CI, 1.14–9.52] and subdistribution HR, 9.29 [95% CI, 3.09–27.99]), heart failure hospitalization (subdistribution HR, 2.11 [95% CI, 1.25–3.55] and subdistribution HR, 3.55 [95% CI, 2.04–6.16]), and adverse outcomes (HR, 2.11 [95% CI, 1.25–3.55] and HR, 3.55 [95% CI, 2.04–6.16]). Modified model for end‐stage liver disease excluding international normalized ratio and controlling nutritional status scores improved the predictive ability of European System for Cardiac Operative Risk Evaluation (area under the curve: 0.80 versus 0.73, P<0.001) and Society of Thoracic Surgeons score (area under the curve: 0.79 versus 0.72, P=0.004) for all‐cause mortality. One year following surgery (n=707), patients with persistent concomitant hepatorenal dysfunction and malnutrition (severe) experienced worse outcomes than those without. Conclusions Concomitant hepatorenal dysfunction and malnutrition was frequent and strongly linked to heart failure and mortality in valvular surgery.